Efficacy of Flavonoids in Increasing Insulin Sensitivity among Pregnant Women with Gestational Diabetes Mellitus: A Systematic Review - Lacorte, Laarni Hannah; Yanga, Jirah Faith; Samson, Kian Steven; Aclibon, Yvan Keith; Buenaventura, Jea Nhycka; Reyes, John Francis Rey Delos; Demabasa, Sarah Lois; Fernando, Ariel Efraim; Laguerta, Cyrelle Jade (Asian Journal of Biological and Life Sciences)
Introduction:Pregnant women can experience a lot of risks and complications during the entirety of the pregnancy with gestational diabetes mellitus (GDM) as one of the most prevalent. Researchers have conducted studies that monitored the conditions of insulin sensitivity among pregnant women as well as determining factors that lead to evaluating the probability of developing gestational diabetes mellitus. Studies on flavonoids have also been conducted to test their efficacy as a source of intervention in preventing the risk of gestational diabetes mellitus.Aim:This paper aims to discuss the various physiological changes and adjustments throughout gestation, and the insulin activity and sensitivity of a pregnant woman with gestational diabetes mellitus. This also aims to give an overview of the interactions and biochemical effects of flavonoids on pregnant women with gestational diabetes mellitus.Methods:There were 277,790 Review Articles garnered from credible sites, such as Google Scholar, MDPI, NCBI, and ScienceDirect that were all published from 2011 up to the present, and only nine (9) were used in this review paper.Results:Flavonoid derivatives (i.e., Flavanones, naringenin, etc.) show normal BMI in varying amounts of flavonoids 718 mg per day and 105 mg per day and are proven to have a lesser risk in developing diabetes among women: type 2 Diabetes and Gestational Diabetes Mellitus. Also, a 24- dietary recall on pregnant women has shown a great contribution in maintaining normal BMI and glucose level [OR 0.62 (95 percent CI 0.38; 0.96)]. In addition, a significant increase in insulin sensitivity is shown in Pregnant women who have taken flavonoids with their derivatives and is associated with NF-κB, Akt, and MAPK Erk1/2 pathways.Conclusion:Upon careful review of the Review Articles, it was observed that there is a significant relationship between the intake of flavonoids and their derivatives in pregnant women with GDM that entails higher insulin sensitivity, consequently lowering the risk of GDM by helping the metabolic pathway metabolism and regulation.
Keywords: Flavonoids; Gestational Diabetes Mellitus; Insulin Sensitivity; Placenta; Pregnant Women